Charuta Narayanganj fine arts institute the new cultural hub: Narayanganj, Dhaka - Zaman, Md. Shadman (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2018.